Gender disparities in clinical presentation, treatment, and outcomes in metastatic spine disease. (February 2021) - Price, Meghan; Goodwin, Jessica C.; De la Garza Ramos, Rafael; Baëta, César; Dalton, Tara; McCray, Edwin; Yassari, Reza; Karikari, Isaac; Abd-El-Barr, Muhammad; Goodwin, Andrea N.; Rory Goodwin, C.
Abstract: Background: The incidence of metastatic spine disease (MSD) is increasing among cancer patients. Given the poor outcomes and high rates of morbidity associated with MSD, it is important to determine demographic factors that could impact interventions and outcomes for this patient population. The objectives of this study were to compare in-hospital mortality and complication rates, clinical presentation, and interventions between female and male patients diagnosed with MSD. Methods: Patient data were collected from the United States National Inpatient Sample (NIS) database from the years 2012−2014. Descriptive statistics were used to compare data from 51, 800 cases; subsequently, multivariable logistic regression analyses were conducted to assess the effect of gender on outcomes. Results: Males had significantly higher rates of in-hospital mortality (OR 1.30; 95 % CI 1.09–1.56, p = 0.004) and were more likely to have received surgical intervention than females (OR 1.34; 95 % CI 1.16–1.55, p < 0.001). Additionally, female patients were more likely to present with vertebral compression fracture (p < 0.001), while metastatic spinal cord compression (MSCC) and paralysis were more common in male patients (p < 0.001). There was no significant difference in rates of in-hospital complications between female and male patients. Conclusion: Given the significant differences in mortality, disease course, treatment, and in-hospital complications between female and male patients diagnosed with MSD, additional prospective studies are necessary to understand how to meaningfully incorporate these differences into clinical care and prognostication going forward.